2022
DOI: 10.59284/jgpeman3
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and its screening: knowledge, attitude and practice among pregnant women in Patan Hospital

Abstract: Introduction: Down syndrome (DS) is the most common cause of intellectual disability among live born children which can be detected prenatally. This study aims to assess the knowledge attitude and practice of pregnant women about Down syndrome and its available prenatal diagnosis.   Method: A study was conducted in Department of Obstetrics and Gynecology of Patan Academy of Health Sciences in 2021.All pregnant ladies who attended the antenatal clinic received a self-administered validated questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…However 72% of the participants in this study believed that DS syndrome is a genetic condition as compared to the present study where more than eighty percent oi the participants answered that A genetic condition caused by an extra copy of chromosome. In one Nepali study the researchers have found that more than half of the pregnant women had poor knowledge of DS and 60% did not have any idea regarding its screening [12]. One study conducted in Sharjah though on pregnant women has reported good knowledge regarding the DS among 64.97% of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…However 72% of the participants in this study believed that DS syndrome is a genetic condition as compared to the present study where more than eighty percent oi the participants answered that A genetic condition caused by an extra copy of chromosome. In one Nepali study the researchers have found that more than half of the pregnant women had poor knowledge of DS and 60% did not have any idea regarding its screening [12]. One study conducted in Sharjah though on pregnant women has reported good knowledge regarding the DS among 64.97% of the participants.…”
Section: Discussionmentioning
confidence: 99%